Pelatihan Desain Grafis Bagi Pengurus Himpunan Mahasiswa dengan Menggunakan Aplikasi Canva Pro - Halilurrahman, M.; Nuriani, Sitti (Journal of Smart Community Service, 2023)
This service activity regarding graphic design training for administrators of student associations using the Canva Pro application is expected to be able to spur and motivate students who are administrators to more quickly understand and practice the use of graphic design applications quickly, reliably and easily and are expected to increase skills. The method used in this service activity is discussion and practice/implementation, the discussion method is used when discussing students' knowledge about graphic design while the practice/implementation method is used to transfer knowledge and skills about the stages of making designs, covers, banners, PDF online using existing templates in the Canva application by taking advantage of existing features. The results of the PKM activities that were carried out were that most of the participants were able to understand and understand even though some were still left behind during practice due to limited facilities, namely the internet network and laptops that were not sufficient, however 9 trainees were able to make their own online curriculum vitae using the canva procapplication.